Static and moving vehicles stability criteria inside floodwaters-a review - Al-Qadami, E.H.H. (International Association of Engineers, 2021)
âVehicles are directly affected by floods and they can be easily swept away once the flow velocity and depth exceed a certain level. Globally, around 50 of the deaths from flooding occur in vehicles each year. Therefore, understanding the vehicleâs behaviors inside floodwaters are of utmost importance. Herein, a comprehensive up to date review was conducted to summarize previous studies on flooded vehicle stability. Several experimental, theoretical, and numerical studies were carried out between 1967 and 2020 using different approaches and methods. For static vehicle, it was noticed that the floating depth ranged between 0.38 m and 0.69 m. However, the sliding stability limits in terms of depth Ã velocity function ranged between 0.3 m2/s and 1.09 m2/s. For moving vehicles, the floating depth found to be 0.45 m, while the depth Ã velocity sliding stability function has not been developed yet. Based on literatures, stability guidelines were proposed for small and large passenger vehicles. The outcomes of this study can be used as guidelines during the planning stages of roads and parking lots to ensure the safety of vehicles during flood events. Â© 2021, International Association of Engineers. All rights reserved.